2003
DOI: 10.1099/mic.0.26275-0
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic-type protein kinases in Streptomyces coelicolor: variations on a common theme

Abstract: The increasing number of genes encoding eukaryotic-type Ser/Thr protein kinases (ESTPKs) in prokaryotes, identified mostly due to genome-sequencing projects, suggests that these enzymes play an indispensable role in many bacterial species. Some prokaryotes, such as Streptomyces coelicolor, carry numerous genes of this type. Though the regulatory pathways have been intensively studied in the organism, experimental proof of the physiological function of ESTPKs is scarce. This review presents a family portrait of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 53 publications
(41 reference statements)
0
50
0
Order By: Relevance
“…AfsK has an N-terminal STK domain and a C-terminal putative sensory portion carrying PQQ domain repeats. These PQQ domain repeats are predicted to form a β-propeller structure similar to WD40 domains and may interact with a ligand, although the general function of PQQ domains is not known (25). Further, AfsK does not have a predicted transmembrane segment, and is reported to be cytoplasmic but loosely associated with the membrane (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AfsK has an N-terminal STK domain and a C-terminal putative sensory portion carrying PQQ domain repeats. These PQQ domain repeats are predicted to form a β-propeller structure similar to WD40 domains and may interact with a ligand, although the general function of PQQ domains is not known (25). Further, AfsK does not have a predicted transmembrane segment, and is reported to be cytoplasmic but loosely associated with the membrane (28).…”
Section: Discussionmentioning
confidence: 99%
“…The S. coelicolor genome carries at least 34 genes predicted to encode STKs (25). Accordingly, we began systematically disrupting these genes, introducing the divIVA allele encoding the Nterminally FLAG-tagged version of the protein into the resulting mutants, and examining the pattern of DivIVA phosphorylation in FLAG-DivIVA/DivIVA mixtures immunoprecipitated from each strain.…”
Section: Diviva Phosphorylation Increases Dramatically When Cell Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…strain PCC 7120 (52; ref. 23), and the Gram-positive soil bacterium Streptomyces coelicolor 24 (34), also produce a large variety of natural products and have complex developmental cycles. These data support the emerging view that ELKs may play an equally important role to histidine protein kinases in modulating prokaryotic behaviors 22 .…”
Section: Phylogenomic Analysis Of S Cellulosum So Ce56mentioning
confidence: 99%
“…Two component systems, consisting of a histidine kinase with a cognate response regulator, are the most abundant signaling systems (5). Recent studies have shown that eukaryotic-type Ser/Thr protein kinases (STKs) also are present in a wide range of prokaryotic genomes and regulate complex and diverse cellular processes (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%